2021
DOI: 10.9734/arrb/2021/v36i230338
|View full text |Cite
|
Sign up to set email alerts
|

Rhizopus spp Promoting and Inducing Late Blight (Phytophthora infestans) Resistance in Solanum lycopersicum L.

Abstract: Tomato (Solanum lycopersicum L) which is highly consumed by humans, suffer severe attacks of various pathogens. Among these pathogens, Phytophthora infestans is the most prominent causing a devastating tomato disease called late blight. This study was aimed at evaluating the protective effects of Rhizopus spp on tomato plant growth upon infection with P. infestans. The work was partition into two phases: phase 1 delt with the effect of Rhizopus spp on tomato growth parameters while phase 2 was on the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results showed that PAL and CAT activity after infection with Cmm significantly increased in treatments with the inoculation of beneficial bacteria B. c -A, as reported by other studies, where the presence of beneficial bacteria such as many species of Bacillus increased biochemical and molecular variables were associated with oxidative stress responses [ 15 , 21 ]. It has been observed that the preventive inoculation of a beneficial microorganism reduces the incidence and severity of an infection by some phytopathogens, increasing total protein and CAT activity [ 22 ]. It has also been found that some bacteria provide protection against Cmm by altering the activity of PAL and total phenolics, decreasing the browning of vascular bundles and the yellowing of leaf [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that PAL and CAT activity after infection with Cmm significantly increased in treatments with the inoculation of beneficial bacteria B. c -A, as reported by other studies, where the presence of beneficial bacteria such as many species of Bacillus increased biochemical and molecular variables were associated with oxidative stress responses [ 15 , 21 ]. It has been observed that the preventive inoculation of a beneficial microorganism reduces the incidence and severity of an infection by some phytopathogens, increasing total protein and CAT activity [ 22 ]. It has also been found that some bacteria provide protection against Cmm by altering the activity of PAL and total phenolics, decreasing the browning of vascular bundles and the yellowing of leaf [ 23 ].…”
Section: Discussionmentioning
confidence: 99%